2012
DOI: 10.1111/j.1466-7657.2012.01022.x
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of globalization to nursing: a concept analysis

Abstract: Several nursing authors argue that nurses globally are increasingly sharing concerns expressed by nurses at a local level. Concerns such as the future sustainability of the profession and more specifically practice concerns such as the continuing failure of nurses to adequately deal with social justice issues requires careful consideration by every nurse. While strategies recommended for dealing with these concerns lack a cohesive thread, some interesting themes and innovative recommendations have emerged. For… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 40 publications
0
31
0
Order By: Relevance
“…[10] This has been explained with medical procession, along with which health care professionals have increasingly concentrated on patients' immediate needs rather than preventative scope including protection of environmental health. [44] In a globalized world, however, sustainable procedures are a necessary characteristic of patient care. [44] Along the topicality and general debate of climate change, health care professionals have become more aware of their environmental burden.…”
Section: Scrutiny Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10] This has been explained with medical procession, along with which health care professionals have increasingly concentrated on patients' immediate needs rather than preventative scope including protection of environmental health. [44] In a globalized world, however, sustainable procedures are a necessary characteristic of patient care. [44] Along the topicality and general debate of climate change, health care professionals have become more aware of their environmental burden.…”
Section: Scrutiny Of the Resultsmentioning
confidence: 99%
“…[44] In a globalized world, however, sustainable procedures are a necessary characteristic of patient care. [44] Along the topicality and general debate of climate change, health care professionals have become more aware of their environmental burden. Despite of this, recent study has reported that nurses seldom expressed pro-environmental attitudes because they were afraid of conflict and stigmatization among their work communities.…”
Section: Scrutiny Of the Resultsmentioning
confidence: 99%
“…Therefore, the challenge presented to health professionals is to develop global thinking at all levels (Kirk, 2002). Nurses have fought for social justice, however paradoxically, despite this deep and meaningful interest in the welfare of the patient there is little consideration for people beyond the immediate care context (Grootjans and Newman, 2012). Grootjans and Newman (2012) describe an 'endemic blindness' to global issues which is not associated with lack of care, but with a poor appreciation of the 'interconnectedness of our planet' and how local actions impact upon global issues.…”
Section: Endemic Blindness To 'Global' Issuesmentioning
confidence: 99%
“…According to our findings, we recommend an ethical framework and nursing actions as useful tools in the efforts to reduce inequities and inequalities in Global Nursing practice (cf. Grootjans & Newman, 2013;Gutierrez et al, 2012;Meum et al, 2013;Wieck, 2003).…”
Section: Discussionmentioning
confidence: 99%